Bi catalysts supported on GaN nanowires toward efficient photoelectrochemical CO2 reduction. Issue 14 (8th March 2022) - Dong, Wan Jae; Navid, Ishtiaque Ahmed; Xiao, Yixin; Lee, Tae Hyung; Lim, Jin Wook; Lee, Donghwa; Jang, Ho Won; Lee, Jong-Lam; Mi, Zetian
Abstract : Bi catalysts supported on GaN nanowires/Si photocathode induce favorable activity toward CO2 reduction to HCOOH. Abstract : Photoelectrodes combined with semiconductors and cocatalysts have been extensively investigated for photoelectrochemical reduction of CO2 gas to chemicals and fuels. However, little attention has been paid to the electronic interaction between semiconductor photoelectrodes and cocatalysts, which is critical for controlling the CO2 reduction reaction. Here, we have discovered that the unique electronic interaction at the interface between bismuth nanoparticles (Bi NPs) and gallium nitride nanowires (GaN NWs) can significantly boost the catalytic activity for the CO2 reduction reaction on a silicon photocathode. Theoretical calculations suggest that the binary system consisting of Bi and GaN favors CO2 conversion to HCOOH and enhances electron transfer from GaN NWs to Bi NPs. The optimized Bi/GaN/Si photocathode results in a superior faradaic efficiency of HCOOH (FEHCOOH ) of ∼98% at −0.3 VRHE under 1-sun illumination.